Action, transcendance, incarnation. Pour une lecture unifiée de la pensée politique de S. Weil - Gabellieri, Emmanuel (Labyrinth, 2023)
In contrast to the readings that oppose a first 'revolutionary' Simone Weil to a second 'conservative' Simone Weil, this article supports the thesis of a profound continuity and coherence in Weil's political thought, parallel to the overall unity of her philosophy. Just as there is no opposition between her political thought of the early and the late 1930s, there is no opposition between her 'mystical' philosophy from the period in Marseille and her "political" philosophy from the period in London. However, this does not abolish the distance that must be maintained between religion, mysticism and politics, because the "synthesis" of these levels is not historical-political, but eschatological. Ultimately, we show that Weilian thought supports both the dual necessity and the mutual insufficiency of mysticism and politics, which enables it to escape both totalitarian idolatry and the mysticism of a pure afterlife. If she ignores the opposition so common in modern thought between "Amor Dei" and "Amor Mundi", it is because she wishes to comply with the dual Platonic and Christian injunction to bring the Good down into necessity without confusing both, thus making political action the criterion of truth of political thought.